Endometrial Preparation for Women Undergoing Embryo Transfer Frozen-Thawed Embryo Transfer With and Without Pretreatment With Gonadotropin Releasing Hormone Agonists - Shohreh Movahedi; Ashraf Aleyasin; Marzieh Agahoseini; Leili Safdarian; Sahar Abroshan; Sepideh Khodaverdi; Parvin Fallahi (Tehran University of Medical Sciences, 2019)
Objective: To evaluate the efficacy of endometrial preparation by exogenous steroids, with and without pretreatment by the use of GnRH agonist. Materials and methods: This randomized interventional study was conducted on 100 women who underwent a FTET that were randomly assigned to receive GnRH agonist (buserelin) in the luteal phase or no receive this medication. In both groups endometrial preparation was achieved by the use of estradiol valerate pill started from the second day of the menstruation and used every day, with an initial dose of 2mg/d and every 3 days increased to 4 mg/d and 6 mg/d, respectively. Endometrial thickness was evaluated by vaginal ultrasound. Forty eight hours after beginning of progesterone administration 2 to 3 embryos surviving in freezing procedure were transferred. Results: the two groups were similar in mean age, body mass index, duration of infertility, type of infertility, number of embryos transferred and endometrial thickness on the day of beginning progesterone therapy. Comparing outcome of FTET between the two groups scheduled for receiving GnRH agonist showed no significant difference in the rate of implantation (6.7% versus 10.0%), the rate of chemical pregnancy (21.7% versus 22.5%), clinical pregnancy rate (15.0% versus 17.5%), and also ongoing pregnancy (13.3% versus 12.5%). Conclusion: Endometrial preparation for FTET using GnRH agonists appears to be as effective as FTET without administrating these agonists.